2014
DOI: 10.1007/s12263-014-0429-z
|View full text |Cite|
|
Sign up to set email alerts
|

Maternal dietary intake of folate, vitamin B12 and MTHFR 677C>T genotype: their impact on newborn’s anthropometric parameters

Abstract: In this study, we evaluated the effects of dietary intake of vitamin B 12 and folate during pregnancy and their interactions with maternal polymorphism of MTHFR (677C[T; 1298A[C) on intrauterine development. Anthropometric parameters were obtained from 231 newborns that belong to a prospective birth cohort in Morelos, Mexico. Maternal dietary intake of vitamin B 12 and folate was assessed using a semi-quantitative questionnaire administered during the first and third trimesters of the pregnancy. Maternal MTHFR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…Although Engel and colleagues did not observe statistically significant associations for MTHFR 677, MTR 2756 and MTRR 66 in the lowest quartile of folate, point estimates of the effect sizes were in the same direction as seen in MTHFR 1298 (OR: 0.6, 0.3 and 0.6 respectively) [ 23 ]. A second folate gene-nutrient interaction study found no significant interaction between maternal dietary folate and MTHFR 677 or 1298 polymorphisms on anthropometric birth parameters ( n = 231) [ 29 ]. This is in contrast to our study ( n = 1873) which showed a significant interaction effect for both of these polymorphisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Engel and colleagues did not observe statistically significant associations for MTHFR 677, MTR 2756 and MTRR 66 in the lowest quartile of folate, point estimates of the effect sizes were in the same direction as seen in MTHFR 1298 (OR: 0.6, 0.3 and 0.6 respectively) [ 23 ]. A second folate gene-nutrient interaction study found no significant interaction between maternal dietary folate and MTHFR 677 or 1298 polymorphisms on anthropometric birth parameters ( n = 231) [ 29 ]. This is in contrast to our study ( n = 1873) which showed a significant interaction effect for both of these polymorphisms.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have examined the influence of folate gene-nutrient interactions on fetal growth outcomes, with inconsistent findings [ 23 , 29 ]. The aim of this study was to use data from the New Zealand participants in the Screening for Pregnancy Endpoints (SCOPE) prospective cohort study to investigate how gene-nutrient interactions between maternal polymorphisms of the folate mediated one-carbon metabolic pathway and maternal FAS are associated with SGA.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, deficient or high-risk individuals could have a special protocol of assessment, diet and treatment regimen. It has been reported that supplemental vitamin B12 during pregnancy significantly improved the size-at-birth for children of maternal carriers of the 677TT genotype (38). Moreover, early genotyping will help in the risk assessment of a certain subset of the population, especially the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Function of MTHFR is needed for the regulation of available 5‐methyl‐THF for homocysteine re‐methylation at the expense of purines and pyrimidine synthesis. SNPs that decrease MTHFR stability and activity are most widely discussed in the context of human pathologies like cancer and neurological disorders as it balances TS synthesis and methylation reactions. The functional MTHFR 677TT genotype decreases the availability of 5‐methylTHF for methylation reactions , reduces global DNA methylation and increases the risk for NTDs .…”
Section: Discussionmentioning
confidence: 99%